Ascending Aortic Aneurysm Repair Combined with Ozaki Procedure: Our First Experience - Gabriyelyan, A.; Beleyovych, V.; Domansky, T.; Beregovoy, O.; Romanova, S.; Kudlay, I.; Chaikovska, S. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Introduction. Aortic valve disease is often combined with the ascending aortic aneurysm. According to a number of authors, the frequency of the diagnosis varies from 9 to 50%, and the condition requires one-stage surgical correction. Typically, in these cases, mechanical or biologic prostheses are used. The Ozaki procedure allows such operations to be performed without replacing the aortic valve with an artificial prosthesis. The aim. To analyze the results of aortic valve reconstruction using the Ozaki technique combined with ascending aortic aneurysm repair. Materials and methods. The article describes the first experience of treatment of 12 patients with aortic valve disease and ascending aortic aneurysm. All the patients underwent Ozaki procedure modified by J. Benedik with surgical correction of aneurysm of the ascending aorta and the aortic arch. Results and discussion. No deaths were observed in the postoperative period. There was no conversion to aortic valve replacement. Ultrasound imaging after 3 and 6 months revealed no aortic valve dysfunction. Clinically, patients’ well-being was satisfactory and they returned to normal life. Long-term results of these operations interventions require further study. Conclusions. Our first clinical experience showed promising short- and medium-term results. The indications for aortic valve reconstruction are the same as those for valve replacement with a bioprosthesis. Ozaki procedure can be successfully combined with ascending aortic aneurysm repair. The main advantage is the absence of a frame that does not narrow the opening area of the valve and preserves the aortic root function, which is very important for patients with a narrow aortic root.